INTEGRASI PERMODELAN ENERGI-LINGKUNGAN DAN LONG RANGE ENERGY ALTERNATIVES PLANNING SYSTEM (LEAP): Kasus Indonesia - Jaka Aminata (Universitas Islam Nahdlatul Ulama Jepara, 2005)
AbstractThe Long-Range Energy Alternatives Planning System (LEAP) is a scenario-based energy environment modeling tool. LEAP as a database, it provides a comprehensive system for maintaining energy information; as a forecasting tool, it enables the user to make projections of energy supply and demand over a long-term planning horizan; as a policy analysis tool, it simulates and assesses the effects - physical, economic, and environmental of alternative energy programs, investments, and actions. Its scenarios are based on comprehensive accounting of how energy is consumed, converted and produced in a given region or economy under a range of alternative assumptions on population, economic development, technology, price and so on. With itsflexible data structures, LEAP allows for analysis as rich in technological specification and end-use detail as the user chooses. In this research, researcher put Indonesian case as